Pelestarian Plasma Nutfah Ubi Kayu Lokal Bangka sebagai Diversifikasi Pangan Lokal - Lestari, Tri (ENVIAGRO, 2014)
Bangka Island is known to have red-yellow podzolic soil type with acid characteristic and is rarely to take as agricultural land. Planting cassava in local area might be a source for local food needs diversify. The purpose of this study was to determine the productivity of the 10 genotypes cassava landrace on red-yellow podzolic soils type. The experiment conducted in the Balunijuk village, Bangka as reference. Experimental design used randomized block design with 10 genotypes Bangka cassava landrace (Upang, Sekula, Bayel, Mentega, Kuning, Batin, Pulut, Sutera, Rakit and Selangor) as treatments. The results showed that 10 genotypes cassava tested produce well on a red-yellow podzolic soils. Morphological analysis performed on tuber parts of Bangka cassava landrace showed outer skin color, skin and tuber flesh color were vary among genotypes. Sutera had the highest tuber production for 2960 g/plant. Cluster analysis based on isozyme markers divided in two groups with similarity coefficient of 0.742. First group consisted of genotype upang, bayel, mentega, pulut, and sutera. Second group consisted of genotype sekula, batin, kuning, rakit, and selangor.